2008
DOI: 10.1038/ng.228
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility variants for male-pattern baldness on chromosome 20p11

Abstract: We carried out a genome-wide association study in 296 individuals with male-pattern baldness (androgenetic alopecia) and 347 controls. We then investigated the 30 best SNPs in an independent replication sample and found highly significant association for five SNPs on chromosome 20p11 (rs2180439 combined P = 2.7 x 10(-15)). No interaction was detected with the X-chromosomal androgen receptor locus, suggesting that the 20p11 locus has a role in a yet-to-be-identified androgen-independent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 15 publications
7
117
0
1
Order By: Relevance
“…Except 6p25.1, all loci have been previously associated with MPB. [14][15][16] The associated SNP at 6p25.1 is a single genome-wide significant finding not supported by additional SNPs in the region and thus warrants further validation.…”
Section: Meta-analysis Of Gwasmentioning
confidence: 90%
See 2 more Smart Citations
“…Except 6p25.1, all loci have been previously associated with MPB. [14][15][16] The associated SNP at 6p25.1 is a single genome-wide significant finding not supported by additional SNPs in the region and thus warrants further validation.…”
Section: Meta-analysis Of Gwasmentioning
confidence: 90%
“…In the present meta-analysis of the three cohorts, the only locus that did not show significant association was 3q25.1, but the allelic effect was in the same direction as Li et al Overall, the observed allele effect sizes were similar between RS and ERF, and similar to previous estimates in other populations. [14][15][16] Noticeable exceptions were: (1) the chromosome 20p11 SNPs showed much smaller effects in RS and ERF (eg, rs6047844 OR = 1.09 in RS and 1.18 in ERF, Table 1) than previous estimations (OR = 1.60 in Li et al and 1.82 in BONN); and (2) the SNPs at the EDA2R/AR locus showed much larger effect (rs1511061 OR = 9.07) in BONN than in RS and ERF (OR 2.68-2.75). These differences are likely explained by the extreme design in BONN, as BONN included only early-onset MPB cases (o40 years of age) and a set of super controls (⩾ 60 years, no signs of MPB) while no MPB pre-selection was made in RS and ERF, in which the majority of the subjects were elderly people.…”
Section: Candidate Snp Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS of traits in humans have shown that most of the associations are to quantitative trait loci (QTL) or risk alleles for complex traits (RACT) that are small to very small in size (Burton et al 2007;Weedon et al 2008). However, GWAS have also identified Mendelian factors causing discrete phenotypes in several species (Klein et al 2005;Karlsson et al 2007;Charlier et al 2008), as well as either discovering, or rediscovering, QTL or RACT of moderate to large effect in humans (Todd et al 1987;Ellis et al 2001;Burton et al 2007;Gieger et al 2008;Hillmer et al 2008;Pollin et al 2008;Benyamin et al 2009;Daly et al 2009). Some of these studies found genetic effects of moderate to large size even though the sample sizes used in those studies were quite small (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least ten published studies presenting methods to explore the predictive values of combinations of SNP alleles of pigmentation phenotypes (skin, eye and hair colour) and presence/absence of freckles [33][34][35][36][37][38][39][40][41][42], two of which [34,40] have already been validated [43][44][45]. Additional research is under development regarding these and other phenotypes, such as estimation of age [46][47][48][49], height [50,51], hair shape [52][53][54], facial features [55,56], baldness [54, 57,58], and adult stuttering [59,60]. Besides physical phenotypes, additional information of individuals can be obtained with some reliability by analysing DNA, such as biogeographical ancestry [61,62] and surname of the sample [6,19,[63][64][65][66][67].…”
Section: Pims For Prediction Of Normal Human Traitsmentioning
confidence: 99%